2010
DOI: 10.1002/aic.12213
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamics design of a carbon dioxide sorption circulating fluidized bed

Abstract: A kinetic theory based hydrodynamic model with experimentally determined sorption rates for reaction of CO 2 with K 2 CO 3 solid sorbent is used to design a compact circulating fluidized bed sorption-regeneration system for CO 2 removal from flue gases. Because of high solids fluxes, the sorber does not require internal or external cooling. The output is verified by computing the granular temperatures, particle viscosities, dispersion, and mass transfer coefficients. These properties agree with reported measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Due to the high-circulation rates, the temperature of the solid sorbent rises only at 4 C. This is similar to the study of Chalermsinsuwan et al 14 This small rise in the solid and gas temperatures keeps the sorption capacity of the solid sorbent relatively constant. The heat of reaction captured in the solid sorbent from the sorber-riser is recovered in the regeneratordowner.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Due to the high-circulation rates, the temperature of the solid sorbent rises only at 4 C. This is similar to the study of Chalermsinsuwan et al 14 This small rise in the solid and gas temperatures keeps the sorption capacity of the solid sorbent relatively constant. The heat of reaction captured in the solid sorbent from the sorber-riser is recovered in the regeneratordowner.…”
Section: Introductionsupporting
confidence: 62%
“…The energy requirement topic is a main issue for this article. Chalermsinsuwan et al 14 showed that the system performance decreases with increasing operating temperature difference between sorber-riser and regenerator-downer. Additionally, the smaller the difference of temperature, the smaller the minimum required power for regeneration process.…”
Section: Solid Sorbent Descriptionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite numerous uncertainties still remaining in terms of hydrodynamic modelling, significant research efforts have recently been invested in extending the KTGF to reactive flows [11][12][13][14][15]. Incorporation of chemical reactions significantly increases the complexity of the system due to the close coupling between hydrodynamics and chemical kinetics [16] and, due to this close coupling, predictions of overall reactor performance are highly dependent on accurate simulation of the underlying hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%